The effects of different salinities level on hatching rate of tiger grouper, epinephelus fuscoguttatus eggs - Cheng Zi Yang (2009)
In order to ·solve the problem of low hatching rate of tiger grouper, E. fuscoguttatus in artificial seed production, an experiment based on eggs hatching rate in different salinity levels was done. The salinity levels used in the experiment were 0, 5, I 0, 15, 20, 25, 30, and 35 ppt. The experiment was conducted in 500ml beaker. The eggs used in the experiment were collected through natural spawning of tiger grouper in the UMS hatchery. Collected eggs were transferred into beaker and acclimatisation process was done to prevent salinity shock to the eggs. At the water temperature of 28°C, tiger grouper eggs did not hatch at the salinity of 0 and 5 ppt. Under the same temperature, the hatching rate of tiger grouper eggs at the salinity of 1 0 ppt was 11.33% ± 12.56. Hatching rate of 21.0% ± 16.82 and 41 % ± 16.82 was achieved at the salinity of 15 and 20 ppt respectively. For the salinity level at 25 ppt, the hatching rate was 48.0% ± 15.07. Hatching rate reached 93.33% ± 3.27 for the salinity level of 30 ppt. The hatching rate reached the highest at the salinity level of 35 ppt which was 98.0% ± 2.53. Better hatching rate can be achieved by culturing tiger grouper eggs in high salinity range from 30 -35 ppt.